2019
DOI: 10.1029/2019je005932
|View full text |Cite
|
Sign up to set email alerts
|

Global Spectral Properties and Lithology of Mercury: The Example of the Shakespeare (H‐03) Quadrangle

Abstract: The MErcury Surface, Space ENvironment, GEochemistry and Ranging mission showed the surface of Mercury with an accuracy never reached before. The morphological and spectral analyses performed thanks to the data collected between 2008 and 2015 revealed that the Mercurian surface differs from the surface of the Moon, although they look visually very similar. The surface of Mercury is characterized by a high morphological and spectral variability, suggesting that its stratigraphy is also heterogeneous. Here, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…Moreover, we compared MDIS measurements with MASCS spectra directly. We used the experiment data record of MDIS-WAC (Hawkins et al, 2007), and applied a radiometric and photometric calibration (Bott et al, 2019;Domingue et al, 2015;Hapke, 1981). Average reflectance obtained in both areas (the original area studied by Vilas et al [2016] and the area observed with MASCS) of the hollows is represented in Figure 10.…”
Section: Mdis and Mascs Comparison Of Hopper's Hollowsmentioning
confidence: 99%
“…Moreover, we compared MDIS measurements with MASCS spectra directly. We used the experiment data record of MDIS-WAC (Hawkins et al, 2007), and applied a radiometric and photometric calibration (Bott et al, 2019;Domingue et al, 2015;Hapke, 1981). Average reflectance obtained in both areas (the original area studied by Vilas et al [2016] and the area observed with MASCS) of the hollows is represented in Figure 10.…”
Section: Mdis and Mascs Comparison Of Hopper's Hollowsmentioning
confidence: 99%
“…Starting from this mosaic, we produced color-composite maps to investigate variations associated with spectral variabilities. For a more in-depth analysis, we defined new spectral parameters, in addition to indices already known from the literature, such as spectral ratios and principal component analysis (see Blewett et al, 1997Blewett et al, , 2007Bott et al, 2019;Denevi et al, 2009). Starting from reflectance and these new indices, we finally define SUs.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced MESSENGER colour image (as Fig. 1) of the Shakespeare quadrangle, H03 (Bott et al 2019). This colour combination emphasises spectral units, such as the 'low reflectance material' (LRM) characterized by low reflectance and low spectral slope (dark blue in this rendering), and faculae (F), thought to be pyroclastic deposits, characterized by high reflectance and high spectral slope (orange in this rendering)…”
Section: Figmentioning
confidence: 96%
“…Planmap and allied efforts are also devoted to integrating morphological and spectral information by redefining geological units, through consideration of colour variation on spectral index maps as well as morphostratigraphic characteristics (e.g., Bott et al 2019;. For example, the spectrally-defined 'low reflectance material' makes up some, but by no means all, of the morphostratigraphically-defined intercrater plains (Fig.…”
Section: Geological and Colour Mappingmentioning
confidence: 99%